Water relations, stomatal responses and physiological changes of Lansium domesticum - Ismail, Mohd Razi; Zainal Abidin, Mohd Idris; Salleh, Ruziah (Universiti Putra Malaysia Press, 1993)
The effects of water stress on growth, water relations and physiological changes of young Lansium domesticum plants were investigated. There was a significant reduction in leaf, stem and root dry weight with increasing water stress. Relative water content was reduced but stomatal density and chlorophyll content were increased with water stress. An increase in stomatal density ofplants subjected to water stress did not improve stomatal functioning as stomatal resistance was greater in these plants. This contributed to the reduction in leaf photosynthesis rate. Stomatal resistance of severely stressed plants did not reach a similar level as plants watered continuously after rewatering. Stomatal resistance of langsat was lower than dokong plants indicating that langsat exhibited a better stomatal control than dokong plants.